FACTORS INFLUENCING EMPLOYEE JOB SECURITY IN JAKARTA: A BASIS FOR FORMULATING HUMAN RESOURCE MANAGEMENT STRATEGIES IN THE DIGITAL TRANSFORMATION ERA - Eric Supandy; Liestyaningrum Rahmadhani Wisnu Putri (Jurnal Ecoment Global, 2026)
Abstract Objective: The goal of this study is to examine how digital literacy, the level of support provided by the organization, opportunities for career growth, and the ability to find employment together affect the sense of job security among employees during Jakarta's digital transformation period. The goal is to establish a solid foundation of evidence to create effective human resource management approaches that can handle the unpredictability and changes in labor needs caused by fast technological development.Design/Methods/Approach: This study employed a quantitative survey method to gather primary data, which was collected through questionnaires distributed to a sample of 167 employees in Jakarta.The participants were between the ages of 18 and 59 and had at least one year of work experience. The data was examined using multiple linear regression analysis in SPSS version 25.This process involved conducting tests for validity and reliability, checking classical assumptions, and performing hypothesis testing with T-tests, F-tests, and analysis of R squared.Findings: The study discovered that digital literacy, support from the organization, opportunities for career growth, and the ability to find employment all have a positive and significant impact on job security. Together, these four factors explain 83% of the differences in how secure employees feel about their jobs. Organizational support was found to be the most significant predictor, with a coefficient of 0.314, followed by employability.Originality/Value: This study presents a distinctive and comprehensive model that explores how both individual skills and organizational elements collectively influence job security, with a specific focus on the workforce in Jakarta. It tackles an important research gap by offering real-world evidence from Indonesia's main economic center, where fast digital changes are greatly affecting the job market, yet this area has not been thoroughly examined before.Practical/Policy implications: Organizations in Jakarta should emphasize thorough human resource strategies that extend beyond technical execution to place greater emphasis on the human aspect. Since organizational support is the main factor that affects job security, management should create environments that are supportive by ensuring open communication, implementing fair policies, and providing consistent feedback. It is important to carry out reskilling, upskilling, and digital literacy initiatives in order to lessen the feeling of job insecurity and support the workforce's ability to adapt over time.